(untitled) (Bangladesh Journal of Child Health, 2020)
Nonalcoholic fatty liver disease (NAFLD) is a disease of liver occurring due to excess accumulation of fat in the liver. For defining NAFLD, there must be evidence of hepatic steatosis (HS), either by imaging or by histology and lack of secondary causes of hepatic fat accumulation. Frequency of NAFLD is increasing worldwide. Overall prevalence of NAFLD in Bangladesh is 33.9%. Insulin resistance is the central factor for the pathogenesis of NAFLD. Most of the children are asymptomatic and are identified incidentally by elevated serum aminotransferases. The objectives of this review are to provide the pediatricians an overview of fatty liver disease in children regarding its etiology, patients’ evaluation and management. This review also provides the approach to a child with fatty liver disease based on the best available evidence from electronic literature searches. Obese (BMI for age > 95th centile) and overweight children (BMI for age between 85th to 95th centile) having additional risk factors like insulin resistance should be routinely screened for NAFLD. Estimation of serum ALT and/ or ultrasonography are the recommended screening tests. Though the treatment of NAFLD includes dietary modifications, physical activities, drugs and surgery; diet and physical activities are the cornerstone of management of NAFLD. Bangladesh J Child Health 2020; VOL 44 (2) :97-103